2021
DOI: 10.1002/dneu.22825
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants at the synapse: Shared phenotypes and converging mechanisms of developmental neurotoxicity

Abstract: The developing nervous system is sensitive to environmental and physiological perturbations in part due to its protracted period of prenatal and postnatal development.Epidemiological and experimental studies link developmental exposures to persistent organic pollutants (POPs) including polychlorinated biphenyls, polychlorinated dibenzop-dioxins, polybrominated diphenyl ethers, and benzo(a)pyrene to increased risk for neurodevelopmental disorders in children. Mechanistic studies reveal that many of the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 247 publications
(406 reference statements)
0
8
0
Order By: Relevance
“…To our knowledge, no previous study has investigated the effects of perinatal dioxin exposure on structural brain changes in humans. Although some previous animal studies reported reduced cortical thickness in several brain areas and changes in cortical cell numbers and cell distributions in TCDD-exposed rats [29,30], recent animal studies suggest that dioxins in low doses may lead to neuronal dendritic overgrowth [22,24], which may in turn lead to increases in brain volume.…”
Section: Global and Regional Brain Volume Alterations Associated With...mentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, no previous study has investigated the effects of perinatal dioxin exposure on structural brain changes in humans. Although some previous animal studies reported reduced cortical thickness in several brain areas and changes in cortical cell numbers and cell distributions in TCDD-exposed rats [29,30], recent animal studies suggest that dioxins in low doses may lead to neuronal dendritic overgrowth [22,24], which may in turn lead to increases in brain volume.…”
Section: Global and Regional Brain Volume Alterations Associated With...mentioning
confidence: 98%
“…We found that opposing effects were associated with high dioxin levels, observing both volume increases and volume decreases. Previous animal studies suggested that the effects of persistent organic pollutants (POPs), including dioxins, might be nonmonotonic: POPs exert both promoting and suppressing effects on neuronal dendritic growth, depending on their dose and the brain region, which may lead to brain volume increases and decreases, respectively [22][23][24].…”
Section: Regional Brain Volume Changes Associated With Blood Dioxin L...mentioning
confidence: 99%
“…Intracellular and extracellular biomarkers provide useful indicators for detecting cellular abnormality, with limits of detection at the range of micromolar to nanomolar levels [ 17 , 18 ]. However, recent studies have shown that chronic exposure to far lower levels of chemicals can induce cellular phenotypic responses [ 19 ]. Additionally, biomarker-based strategies are generally expensive and require the multi-step processing of cells, limiting their application in high-throughput detection [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…CYPs can also metabolically activate and detoxify several xenobiotics which enter the brain, as well as play important functions in brain homeostasis and disease. Indeed, a feature of most AhR ligands is their lipophilic nature, which allows them to cross the blood-brain barrier and affect brain physiology [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%